The Continuity and Quality of Primary Care. (October 2013) - Maciejewski, Matthew L.; Wang, Virginia; Burgess, James F.; Bryson, Chris L.; Perkins, Mark; Liu, Chuan-Fen
Patients who have access to different health care systems, such as Medicare-eligible veterans, may obtain services in either or both health systems. We examined whether quality of diabetes care was associated with care continuity or veterans' usual source of primary care in a retrospective cohort study of 1, 867 Medicare-eligible veterans with diabetes in 2001 to 2004. Underprovision of quality of diabetes care was more common than overprovision. In adjusted analyses, veterans who relied only on Medicare fee-for-service (FFS) for primary care were more likely to be underprovided HbA1c testing than veterans who relied only on Veteran Affairs (VA) for primary care. Dual users of VA and Medicare FFS primary care were significantly more likely to be overprovided HbA1c and microalbumin testing than VA-only users. VA and Medicare providers may need to coordinate more effectively to ensure appropriate diabetes care to Medicare-eligible veterans, because VA reliance was a stronger predictor than care continuity.